HUBUNGAN ASUPAN BESI HEME DAN NON-HEME KADAR FERRITIN PADA CALON PENGANTIN PEREMPUAN DI KOTA PADANG - Ulya Uti - Fasrini; Wiyola Audina; Defrin Defrin; Desmawati Desmawati; Hudila Rifa Karmia; Abdiana Abdiana (Poltekkes Kemenkes Padang, 2021)
Women of childbearing age are prone to anemia, especially iron-deficiency anemia. The outcome might be seen in the high maternal mortality rate in the Padang city (16 cases. Serum ferritin can be used as an initial indicator to determine iron deficiency. A decrease in serum ferritin levels can be influenced by iron intake. This study aimed to determine the relationship between heme and non-heme iron intake with ferritin serum concentration in women’s bride candidates in Padang City. This analytical study with a cross-sectional design involved 30 bride candidates, 20-30 years old. Iron intake were collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and serum ferritin levels were measured using the Enhanced ChemiLuminescence Immuno Assay (ECLIA) method. Data were analyzed using the Pearson correlation coefficient test. The results showed the mean of heme and non-heme iron intake was 2.76 ± 0.90 mg/day and 3.83 ± 0.97 mg/day, respectively, and the mean of serum ferritin levels was 46.27 ± 27.61 ng/ml. The test showed no significant correlation between heme (r=0.094, p=0.622) and non-heme iron (r=-0.179, p=0.345) intake with serum ferritin levels. This study concludes that there is no relationship between heme and non-heme iron intake with serum ferritin levels on bride candidates in Padang City. Therefore, to prevent the incidence of anemia during pregnancy, it is highly recommended for the brides to increase their iron intake from both animal and vegetable sources.